2008
DOI: 10.1021/jp801461x
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Refraction and Absorption Phenomena in a Novel Nanocomposite Based on a Dye Stabilized in a Solid Hybrid Matrix

Abstract: Nonlinear optical behavior of a novel nanocomposite material based on chloroaluminum phthalocyanine (ClAlPc) embedded in silica and incorporated in the structural nanopores of a Nafion membrane is investigated using the Z-scan technique. The experiments are performed at 532 nm using 8 ns pulses at a pulse repetition rate of 10 Hz from a frequency-doubled Nd:YAG laser. The nonlinearity in the hybrid membranes is characterized by obtaining the nonlinear refractive index and nonlinear absorption coefficient. Fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Under such circumstances the normalized transmittance curve exhibits a completely symmetric shape about the waist (z = 0). At present, the open-aperture Z-scan model is widely used for the nonlinear optical absorption of materials [7][8][9][10][11]. In particular, some studies revealed that many materials exhibit more than one kind of nonlinear optical absorption simultaneously with the change in the input light intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Under such circumstances the normalized transmittance curve exhibits a completely symmetric shape about the waist (z = 0). At present, the open-aperture Z-scan model is widely used for the nonlinear optical absorption of materials [7][8][9][10][11]. In particular, some studies revealed that many materials exhibit more than one kind of nonlinear optical absorption simultaneously with the change in the input light intensity.…”
Section: Introductionmentioning
confidence: 99%